Dampak Digitalisasi, Religiusitas, dan Keterikatan Pegawai terhadap Kinerja Pegawai Keuangan Syariah di Kota Banda Aceh: Peran Kepatuhan Syariah sebagai Variabel Moderator - Ismail; Iqbal, Taufiq; Mujiburrahman (Jurnal Manajemen dan Teknologi, 2025)
This study aims to analyze the impact of digitalization, religiosity, and employee engagement on the performance of employees in Islamic financial institutions in Banda Aceh, with Sharia compliance acting as a moderating variable. Digitalization in the Islamic finance sector enhances employee performance, particularly in the Small and Medium Enterprises (SMEs) sector, through operational efficiency and easier access to information. Religiosity plays a significant role in improving employee performance as the application of religious values in work strengthens commitment and motivation. High employee engagement, including satisfaction and loyalty to the organization, also contributes to better performance. Sharia compliance, as a moderating variable, strengthens the relationship between digitalization, religiosity, employee engagement, and performance. This study uses a quantitative approach with surveys administered to employees in Islamic financial institutions in Banda Aceh. The analysis results show that digitalization, religiosity, and employee engagement positively influence employee performance, while Sharia compliance strengthens these effects. These findings provide a deeper understanding of how technology, religious values, and employee involvement influence performance in Islamic financial institutions and highlight the importance of Sharia compliance in enhancing operational effectiveness.